Oxidative Stress as Estimated by Gamma-Glutamyl Transferase Levels Amplifies the Alkaline Phosphatase-Dependent Risk for Mortality in ESKD Patients on Dialysis - Torino, Claudia (Oxid Med Cell Longev, 2016)
Alkaline phosphatase (Alk-Phos) is a powerful predictor of death in patients with end-stage kidney disease (ESKD) and oxidative stress is a strong inducer of Alk-Phos in various tissues. We tested the hypothesis that oxidative stress, as estimated by a robust marker of systemic oxidative stress like γ-Glutamyl-Transpeptidase (GGT) levels, may interact with Alk-Phos in the high risk of death in a cohort of 993 ESKD patients maintained on chronic dialysis. In fully adjusted analyses the HR for mortality associated with Alk-Phos (50 IU/L increase) was progressively higher across GGT quintiles, being minimal in patients in the first quintile (HR: 0.89, 95% CI: 0.77–1.03) and highest in the GGT fifth quintile (HR: 1.13, 95% CI: 1.03–1.2) (P for the effect modification = 0.02). These findings were fully confirmed in sensitivity analyses excluding patients with preexisting liver disease, excessive alcohol intake, or altered liver disease biomarkers. GGT amplifies the risk of death associated with high Alk-Phos levels in ESKD patients. This observation is compatible with the hypothesis that oxidative stress is a strong modifier of the adverse biological effects of high Alk-Phos in this population.